A Systematic Literature Review (SLR) on Stakeholder Dynamics in Indonesia Tourism Recovery Post-Pandemic - Muzdalifa, Fairuz; Novianti, Evi Novianti; Hadian, Mohammad Sapari Dwi; Prihadi, Donny Yuliandri; Yustikasari, Yustikasari (Universitas Sultan Ageng Tirtayasa, 2025)
The COVID-19 pandemic has changed the dynamics of the tourism sector, driving the need for a sustainable and inclusive recovery approach. This study conducted a systematic literature review (SLR) to analyze the dynamics of stakeholders in post-pandemic tourism recovery in Indonesia, using the Pentahelix framework. The study found that collaboration between government, academia, industry, communities, and the media is key to driving sustainability and resilience in the tourism sector. The findings suggest that while challenges, such as differing priorities, resource constraints, and communication barriers, hamper the effectiveness of collaboration, strategies such as strengthening communication, leveraging technology, and clear role-sharing can improve recovery outcomes. The study emphasizes the importance of cross-sector collaboration in building a more resilient, inclusive, and sustainability-oriented tourism in the future.